Silent Corticotroph Tumor with Adrenocortical Choristoma in an Eleven-year-old Boy - Hande Turan; Gürkan Tarçın; Özgür Mete; Ada Bulut Sinoplu; Saadet Olcay Evliyaoğlu; Büge Öz; Oya Ercan (Galenos Yayincilik, 2022)
Silent corticotroph tumors are composed of corticotroph cells, but do not manifest any biochemical or clinical evidence of hypercortisolism. A choristoma is a benign, congenital proliferation of histologically mature tissue elements normally not present at the site of occurrence. The existence of adrenocortical cells within the pituitary gland, which can be explained as a choristoma, is a very rare entity, and the co-occurrence of these two entities have only been reported in few cases. We report an 11-year-old boy with central hypothyroidism. On cranial magnetic resonance imaging a pituitary tumor was detected, and histopathological studies led to a diagnosis of an adrenal choristoma and a silent corticotroph tumor in the pituitary gland. The presence of adrenocortical cells were confirmed by positive calretinin, inhibin and Melan A staining, and the corticotroph cells by immunohistochemistry demonstrating adrenocorticotropic hormone positivity. Herein, we report the fourth and the youngest case of silent corticotroph tumor with adrenocortical choristoma in the literature. Even though the underlying mechanism is not fully understood, suggested mechanisms are discussed.